Political Ideologies and Worldviews An Introduction - Vézina, Valérie (Open textbook library., 2021)
Political Ideologies and Worldviews: An Introduction takes a “pluralist” approach and, in addition to being the first open textbook on its subject, also pushes back against the Eurocentric tendencies of standard textbooks by including chapters on Indigenous worldviews and Confucianism. Providing the latest scholarship on “classical ideologies” (liberalism, conservatism, socialism, anarchism, etc.), the textbook also includes innovative chapters on populism, feminism, and multiculturalism, as well as looking at the future of ideologies in a globalized world. Joining together scholars from Canada and beyond, the text also contains discussion questions to help students and readers to think further. This edited open textbook will be a great asset for introductory courses at the college and university levels on political ideologies and political thought and philosophy, but could also be used in other disciplines, as each chapter assesses the state of the ideology in today’s world. The general reader looking for a better understanding of the competing ideological currents of our time – currents which flow into our daily political debates and real-life government decisions – will also greatly benefit from this book.